THE ETHICS OF PLATO’S IDEAS AND IDEALS - Jonas Balčius (Problemos)
This work rests on the assumption that Plato as ethic is undeservedly ignored. He is traditionally considered to be the author of objective philosophical idealism. A more careful analysis proves that the famous scholar of antiquity is primarily the author of ontoethical philosophical conception. His essential philosophical convictions are very close to those of his teacher and greatest authority, Socrates. The later maintained that the true objects of philosophical studies were society and individuals together with their ethical orientations. Plato supplemented these ideas with the ontoethical conception of universum. This helps one understand his theory of "ideas": according to the Greek world view, nature, in its totality, was not only considered to be beautiful and harmonious, but also sensible. So the ideas of Good, Beauty, Truth, and Justice became the real reason of the world’s existence. A new aspect of Plato’s world view is his retributionalistic conception, according to which every person’s life is assessed after death. In this sense, Plato is the author of religious ethics.